ANALISIS PENGAJARAN FONETIK DALAM MENINGKATKAN PELAFALAN: PERSPEKTIF GURU DAN SISWA - Dika Sabilla; Nissa Zahra Silmy Damanik; Chairunnisa S; Darma Subianto (Jurnal Sathar, 2025)
Good pronunciation ability is one of the important aspects in language acquisition, especially for foreign language learners. This study aims to analyse the effectiveness of phonetic teaching in improving students' pronunciation from the perspective of teachers and students. Qualitative method was used in this study with data collection techniques in the form of in-depth interviews, classroom observations, and documentation. The study involved several language teachers and students at the secondary level who participated in phonetics-based learning. The results showed that the phonetic teaching method significantly helped students in improving the pronunciation of sounds that were not present in their mother tongue, such as the sounds /θ/ and /ð/. Teachers stated that phonetic teaching provides a clear framework to help students understand the relationship between sounds and phonetic symbols. However, the main challenges faced were limited time to practice pronunciation in depth and students' difficulty in understanding phonetic symbols consistently. Meanwhile, students felt this method increased their confidence in speaking a foreign language, although it required more practice outside the classroom. This research emphasises the importance of integrating phonetic teaching methods in language learning, with technological support and continuous practice to overcome the challenges. The results of this study are expected to contribute to the development of more effective language learning strategies, particularly in improving students' pronunciation aspects.